Disseminated extragenital bullous lichen sclerosus - Tu-Van T Trinh; Karina Parr; David F Butler (Wolters Kluwer Medknow Publications, 2014)
Lichen sclerosus commonly affects the genitalia of post-menopausal women. We describe a woman with painful, disseminated, bullous, extragenital lichen sclerosus that responded to oral acitretin and topical calcitriol and triamcinolone.